Investigating the Efficacy of Reading Adventure Time! for Improving Reading Skills in Children with Visual Impairments. (March 2020) - Kamei-Hannan, Cheryl; McCarthy, Tessa; D'Andrea, Frances Mary; Holbrook, M. Cay
Introduction: Reading Adventure Time!, formerly known as the pilot version of the iBraille Challenge Mobile App, is an educational technology tool integrating digital literacy to support braille reading and writing instruction for students in 1st–12th grades. Designed to operate on an Apple iPad with a refreshable braille display, Reading Adventure Time! uses gaming strategies to motivate students to improve literacy skills such as fluency, comprehension, writing dictation, and proofreading. Methods: The application (app) was developed under a Stepping Up Technology grant (H327S120007), which was disseminated to more than 50 teachers and students. Teachers and caregivers completed a Likert-type scale of technology skills as a pre- and postmeasure. Students' reading speed, comprehension, and miscues were measured by the app. Results: Over 50 participants who used the app showed gains in reading and technology skills. Discussion: Students' reading speeds, as measured by the app, mirror the reading speeds found in prior research (e.g., the ABC Braille Study). The impact on technology skills for teachers, caregivers, and students was much greater than anticipated. Implications for practitioners: The study provides evidence supporting Reading Adventure Time! as a supplemental intervention that addresses several reading skills and may be used in conjunction with a total, balanced literacy program.